Laser beam profiling : cost-effective solutions - Kallepalli, Akhil; James, David B. (Ph. D.) (IOP (Series). Release 22., 2022)
This book provides an overview of lasers, silicon sensors, and practical solutions to beam profiling which has never been presented in a single text. Understanding laser beam characteristics before and after interaction with an object provides intrinsic insights into the nature of the object.